Pengaruh Ukuran Perusahaan Dan Likuiditas Terhadap Profitabilitas - Diah Nurdiana (Menara Ilmu, 2018)
The purpose of this research is to know: Influence of Company Size on Profitability, InfluenceLiquidity to Profitability, Influence of Company Size and Liquidity to Profitability at Real Estateand Property firms listed on BEI period 2011-2015.The sample of the company is taken by purposive sampling method where the sample is taken asmany as 8 companies from 47 real estate and property companies listed on BEI in period 2011-2015. The method of analysis used in this study is multiple linear regression analysis and classicalassumption test. Hypothesis testing is done by using t test and test f.The results of this study indicate that partially, Corporate Size Variables have no significant effecton Profitability seen from t arithmetic 1.319 smaller than t table 1.687. While Liquidity Variablesignificantly influence to Profitability seen from titung 2,176 bigger than t table 1,687.Simultaneously, Varabel firm size and liquidity have significant effect simultaneously onProfitability, can be seen from Fcount> Ftable (5,015> 3,28) with significance equal to 0,012greater than 0,05.Keywords: Company Size, Likudity, Profitability (ROA).